Diplomacy of European States and the Revolution of 1830 in Belgium - Oksana V. Zhidkova; Elena A. Popova (RUDN Journal of World History, 2024)
The nature of interstate and international relations in the post - Napoleonic period was determined at the Vienna Congress of 1814-1815. Maintaining peace and stability in Europe, preserving the legitimacy of the ruling dynasties and controlling the balance of power were considered one of the main tasks of the Vienna system of international relations. The main obstacles to compliance with these principles were the revolutionary events of 1820-1830, which arose in different regions of Europe. The response to the “challenges” of the new system of international relations was both diplomatic and military measures to maintain the status quo of European states. The purpose of the article is to analyze the positions of the leading European states at the initial stage of the revolution in Belgium, which began in August 1830. In the context of the growing revolutionary crisis in Europe, it is important to understand what motives guided the Russian, French, Austrian, Prussian and English sides in developing their positions, what were the motives of their foreign policy in Belgium and how they influenced multilateral relations during the Belgian revolution. The study of the diplomatic correspondence of representatives of European countries through the channels of foreign ministries made it possible to identify the differences that existed between Russia, England, France, Austria and Prussia on the Belgian issue, to trace the changes in the positions of the countries in the process of developing a joint solution. An analysis of the process of European countries making decisions about the future of Belgium showed the desire of the participants of the “European concert” to comply with the principles of the Vienna system of international relations.